Antiviral Immunological Potential of Male Papaya (Carica papaya L.) Leaf Extract Through Activation of the Type I Interferon Pathway - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo (Biology, Medicine, & Natural Product Chemistry, 2026)
Viral infections remain a major global health challenge, highlighting the need for novel host-directed antiviral strategies. Activation of the type I interferon pathway represents a critical component of innate antiviral immunity. Male papaya (Carica papaya L.) leaves have been traditionally used to enhance immunity; however, their antiviral immunological mechanisms remain insufficiently characterized. This study aimed to investigate the antiviral immunologic potential of male papaya leaf extract by activating the type I interferon signaling pathway. Male papaya leaves were extracted using 70% ethanol, and phytochemical screening was performed. The immunomodulatory activity of the extract was evaluated in RAW 264.7 and THP-1 cells stimulated with polyinosinic-polycytidylic acid [poly(I:C)] as a viral mimic. Cytotoxicity was assessed using the MTT assay. Type I interferon production (IFN-alpha and IFN-beta) was quantified by ELISA, while activation of interferon signaling was evaluated by analysis of interferon-stimulated gene expression using quantitative real-time PCR and signaling protein activation by Western blot. The extract showed no significant cytotoxicity at concentrations up to 200 µg/mL. Treatment with male papaya leaf extract significantly enhanced IFN-alpha and IFN-beta production in poly(I:C)-stimulated cells in a dose-dependent manner. This increase was accompanied by activation of IRF3 and STAT1 signaling and robust upregulation of interferon-stimulated genes, including MX1, OAS1, and ISG15. These findings indicate that the extract enhances antiviral immune responses by amplifying type I interferon-mediated signaling. In conclusion, male papaya leaf extract exhibits significant antiviral immunological activity through activation of the type I interferon pathway. This host-directed immunomodulatory mechanism supports its potential development as a complementary therapeutic agent for viral infections.